Model Implementasi kebijakan Satuan Pendidikan Aman Bencana (SPAB) Berbasis Karakteristik Ekologis Lahan Basah (Studi Analisis Di Kota Barjarmasin Dan Kabupaten Banjar) - Bambang Dedi Mulyadi; Aslamiah Aslamiah; Novitawati Novitawati (Jurnal Ragam Pengabdian, 2026)
The Disaster-Safe School (SPAB) policy in Indonesia is nationally designed to integrate Disaster Risk Reduction (DRR) into the school ecosystem. However, the standard implementation of this policy is often one-size-fits-all and biased towards geological disaster mitigation, making it inadequate when applied to specific regional characteristics. This study aims to evaluate the implementation of SPAB and construct a new, adaptive policy model in wetland ecological areas. Employing a qualitative method with an explanatory case study approach, this research focuses on Banjarmasin City and Banjar Regency in South Kalimantan Province. The analysis of the three pillars of SPAB reveals a failure in infrastructure adaptation to hydrometeorological disasters (tidal and river floods), rigidity in disaster-responsive budget governance, and curriculum dissonance in disaster education that ignores local wetland wisdom. As a novelty, this research formulates the "Contextual Wetland SPAB Policy Implementation Model." This model recommends interventions such as aquatic architectural adaptation, decentralization of school mitigation emergency funds, and the localization of a DRR curriculum based on cyclic threats. This model is expected to serve as a strategic reference for formulating educational resilience policies in areas characterized by wetlands and waterway.